A reversal of the shift towards earlier spring phenology in several Mediterranean reptiles and amphibians during the 1998-2013 warming slowdown - Prodon, Roger (Global change biology, 2017)
Published 2017. This article is a U.S. Government work and is in the public domain in the USA.